(untitled) (Journal of Multidisciplinary Sciences and Innovations, 2025)
This article examines the improvement of mechanisms for applying creative approaches in the process of developing professional qualities in students. The study highlights the importance of creativity as a decisive factor in preparing highly qualified specialists who are capable of adapting to rapidly changing socio-economic conditions. By analyzing theoretical foundations and practical experiences, the research proposes mechanisms aimed at integrating innovative teaching methods, problem-based learning, and project-oriented education into the higher education process. The results demonstrate that the application of creative approaches not only enhances professional competence but also fosters independent thinking, teamwork, and decision-making skills among students. The study contributes to the field of pedagogy by offering scientifically grounded recommendations for the systematic development of professional qualities in students through creativity-driven methods.